Subsidence above depleted gas fields. Issue 3 (5th May 2015) - Santagiuliana, Raffaella; Fabris, Massimo; Schrefler, Bernhard Aribo
Abstract : Purpose: – The purpose of this paper is to give an explanation of the new data available about surface subsidence above the depleted gas reservoir Ravenna Terra. These data confirm the existence after end of exploitation of a reversed subsidence bowl with minimum subsidence above the reservoir, as opposed to conventional subsidence bowls during exploitation which show maximum subsidence in the same location. Design/methodology/approach: – The paper analyses these new data about the existence after end of exploitation of a reversed subsidence bowl. The observed behaviour is reproduced successfully with a fully coupled two phase flow code in deforming reservoir rocks which incorporates a constitutive model for partially saturated porous media. Findings: – The paper provides successful simulations. These allow affirming with confidence that the explanation for the peculiar behaviour is reservoir flooding and partially saturated rock behaviour. Research limitations/implications: – Further research: other case studies where similar behaviour is expected, e.g. Ekofisk. Practical implications: – The paper includes implications for better management of reservoir exploitation schedules to minimize the observed phenomenon. Originality/value: – This paper explains the peculiar behaviour of subsidence above the depleted gas reservoir Ravenna Terra and confirms the conjecture that constitutive behaviour of partially saturated rocks is the origin of the observed phenomenon.